Respuesta :

Answer: I GOT YOU!!!

Step-by-step explanation:

I hope this helps you let me know by saying thanks Have a great day

Ver imagen Аноним

The recursive rule of the sequence is [tex]a_n = 2 * a_{n-1} +a_{n - 2}[/tex] and the 7th term is 268

The recursive rule of the sequence

The sequence is given as

{2,3,8,19,46,...}

So, we have:

  • 2 = 2 * 1 + 0
  • 3 = 2 * 1 + 1
  • 8 = 2 * 3 + 2
  • 19 = 2 * 8 + 3
  • 46 = 2 * 19 + 8

Following the above sequence, the nth term of the sequence is:

[tex]a_n = 2 * a_{n-1} +a_{n - 2}[/tex]

For a7, we have:

[tex]a_7 = 2 * a_{7-1} +a_{7 - 2}[/tex]

This gives

[tex]a_7 = 2 * a_{6} +a_{5[/tex]

Substitute known values

[tex]a_7 = 2 * a_{6} +46[/tex]

a6 is calculated using:

[tex]a_6 = 2 * a_{5} +a_4[/tex]

So, we have:

[tex]a_7 = 2 * (2 * a_{5} +a_4) + 46[/tex]

Substitute known values

[tex]a_7 = 2 * (2 * 46 +19) + 46[/tex]

Evaluate

a7 = 268

Hence, the recursive rule of the sequence is [tex]a_n = 2 * a_{n-1} +a_{n - 2}[/tex] and the 7th term is 268

Read more about sequence at:

https://brainly.com/question/24643676